Greenhouse autoduina - Syed Ahmad Syafiq, Tuan Nek (2014)
An automated system is a system that is used to reduce the need for human work in the production of goods and services. The biggest benefit of automation is that it saves labor. However, it is also used to save energy and materials and to improve quality, accuracy and precision. Automation system can be applied to the greenhouse irrigation system because of many reasons. With automation system everything can be done systematically, efficiently while saving a lot of cost' factor such as money, energy and time. The use of microcontroller in the automation system has been broad nowadays because of it capability. Arduino is a one good microcontroller to use in the Greenhouse Autoduino because of the many good reason it provides. On the other hand, Microcontroller is a highly integrated chip that contains all the components comprising a controller. Typically this includes a CPU, RAM, some form of ROM, I/O ports, and timers. Unlike a general-purpose computer, which also includes all of these components, a microcontroller is designed for a very specific task such as to control a particular system. As a result, the parts can be simplified and reduced, which cuts down on production costs as mention earlier.